Desenvolvimento de um aplicativo mobile gamificado para o engajamento em aulas de educação física - Parizotto, Diego (2019)
This article aims to provide a tool to assist teachers, enabling them to use it to contribute to student engagement with the proposed activities. Initially, an analysis of gamification techniques was conducted, examining how they can be used in an application and how they affect user motivation. Subsequently, the app was developed using the previously studied gamification techniques; its functionality is then described in this article.